PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE ACTIVE DEBATE DAN METODE DISKUSI TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN PKN DI KELAS XI SMA NEGERI 7 PALU - Nurainun, Nurainun (Katalogis, 2016)
Learning using Cooperative Learning model of the type Active Debate to train students to think critically through debate. Discussion method to train students interact in solving a problem. This study aimed to determine whether there is a difference increase critical thinking skills of students in classes that implement Cooperative Learning model ot the type of Active Debate and discussion class that implements the method. Sample in this research is class student XI IPS I as an experimental class and class XI IPA III as the control class. Date collection techniques are criticalÂ  thinking skills test. Based on research results of students critical thinking skills after study shows that there are differences in students critical thinking abilities experimental class and control class. It can be concluded that the class usingÂ  Cooperative Learning model of the type of Active Debate has the ability to think critically is better than the class that uses the mothod of discussion.